Android-Based Mobile Learning Application Development to Enhance Programming Skills in Vocational High School Students of Informatics Engineering - fajriyah fajriyah; Rohaili Rohaili (Molang: Journal Islamic Education, 2026)
Programming skill is a core competency in Vocational High School (SMK) Informatics Engineering programmes, yet students consistently struggle with it due to limited learning resources and inadequate interactive media. This study developed and evaluated an Android-based Mobile Learning (M-learning) application to enhance programming skills among SMK Informatics Engineering students. The Software Development Life Cycle (SDLC) model guided development across five phases: requirements analysis, system design, implementation, testing, and evaluation. The application integrates a multimodal theory content module and a gamified practice module. Qualitative data were collected through in-depth interviews and structured observation with purposively selected students over a four-week trial period, then analysed using inductive content analysis in NVivo 14. Four themes emerged: ease of use, accelerated comprehension of programming concepts, increased motivation for self-directed study, and clear preference over conventional learning resources. Triangulated evidence indicated meaningful improvement in programming performance. These findings support Android-based M-learning as an effective, flexible supplement to conventional programming instruction in SMK contexts; however, longitudinal studies with larger samples are warranted.